Geosites in the Gole della Breggia Geopark, Ticino, Southern Switzerland - Paolo Oppizzi; Federico Pasquaré Mariotto; Rudolf Stockar; Andrea Stella; Noemi Corti; Martina Pedicini; Sergio Andò; Giovanni Vezzoli; Fabio Luca Bonali (Resources, 2023)
This work is aimed at illustrating one of the most engaging geoparks in Europe, the Gole della Breggia Geopark. By following its geotrail, the visitors can observe a great deal of features that encompass a wide variety of sedimentary, stratigraphic, tectonic and paleogeographic processes. Its contents are popularized by a comprehensive geotrail that encompasses 23 geostops, enriched with explanatory panels, which enable viewers to gain an overall picture of the complex processes that led to the present-day configuration of the outcrops encountered in the geopark. We have selected five significative outcrops, which we have regarded as fully-fledged geosites, and which encompass the whole 170-million-year interval, from Early Jurassic to Late Miocene times, during which the rocks of the geopark were deposited and deformed. We have performed an assessment of the five geosites, using the most common criteria that can be applied for geosite evaluation. The results of the assessment show that the most valuable geosites are the Lombardian Maiolica, and the Limestone with Pelagic Bivalves. All five geosites, thanks to a QR code added to each figure along the text, can be viewed as virtual geosites (VGs), integrated by 360° videos.